Many Body Interactions on Lattice Vibrational Properties of Plutonium Arsenides - Imran Aziz, Md.; Ahmed, Irfan (Asian Journal of Chemistry, 2011)
Many body interactions, which includes the effect of van der Waals interactions (vWI) and three body interactions in the framework of rigid shell model, has been employed to study the lattice dynamics of plutonium arsenides. It is assumed that the overlap repulsion is effective only up to the first neighbour, while the van der Waals attraction acts up to the second neighbours and plays very important role. Because of f-d hybridization, the large LO-TO phonon splitting at zone centre predicted. The agreement between our predictions and available neutron data for phonon dispersion curves strongly supports the inclusion of van der Waals interactions. We also report the specific heat variations, two phonon IR/Raman spectra of plutonium arsenides.